STUDI PEMBENTUKAN ZONE JARINGAN PIPA DISTRIBUSI AIR MINUM KOTA SEMARANG (Wilayah pelayanan PDAM SEMARANG UTARA ) - Nasrullah Nasrullah,; Mochamad Arief Budihardjo (Diponegoro University, 2007)
Semarang City’s drinking water distribution system in the North Semarang uses an interconnectionnetwork system. This causes difficulty in optimizing the network distribution supply and controlling thewater leakage. Semarang City’s drinking water provider is planning to divide the area in to 25 zones. Thisstudy purpose to plan one of the zone areas, which is zone 1. The existing condition on zone 1 shows thatthe water source is from Siranda distribution reservoir. The water flows by the gravitation. The distributionpressure on the pipe network is not even. Pressure drop between 3 to 7 m water columns at the peakcondition on the end of the furthest point in the network. The strategy in planning the network is by cuttingthe interconnection pipe, providing new pipes, closing the existing valves, adding new valves for isolatedareas, adding primary water meter and sub zone water meter and moving the interconnection pipes. Then,the distribution system is analyzed using Epanet 2.0 program that can show the effort of the changes after.The system shows that there is no more pressure drop on the area. The pressures are between 11-16 meterwater column and the water flow in the pipes are more alike, between 0,3 to 3 m/s. The PDAM can observethe distribution and the water leak more easily by using this system.